Attitude for vaccination prophylaxis among pregnant women: a cross-sectional study. Issue 1 (31st January 2022) - Bianchi, Francesco Paolo; Stefanizzi, Pasquale; Lattanzio, Sabrina; Diella, Giusy; Germinario, Cinzia Annatea; Tafuri, Silvio
ABSTRACT: Pregnant women and newborns are considered a subgroup of population at increased risk for several infectious diseases, some of which are vaccine-preventable. Anti-diphtheria-tetanus-pertussis vaccine (dTpa) and influenza vaccine are recommended for pregnant women. We carried out a study to evaluate the knowledge of new mothers toward the main vaccine-preventable diseases and to assess their compliance with recommended vaccinations. Using the Hospital Discharge Forms (SDO), the list of women who gave birth in 2018 was generated. Women were interviewed by a questionnaire administered by telephone. The study sample consisted of 145 subjects, with an average age of 35.0 ± 5.9 years (range = 18.0–47.0). 5/145 (3.4%; 95% CI = 1.1–7.9%) subjects were advised during pregnancy to have the flu shot; only 1/145 (0.7%; 95% CI = 0.5–71.6%) reported the flu vaccine during the last pregnancy. 94/145 (64.8%; 95% CI = 57.2–73.2%) respondents declared that they had carried out the TORCH panel exams before pregnancy; of these 18/94 (19.2%; 95% C = 11.8–28.6%) were susceptible for rubella. Of these subjects, for 7/18 (38.9%; 95% CI = 17.3–64.3%) rubella vaccination was offered and 5/7 (71.4%; 95% CI = 29.0–96.3%) decided to carry out the vaccination. Only 1/145 (0.7%; 95% CI = 0.0–3.8%) of the interviewed woman underwent anti-dTap vaccination. Greater efforts must be made by public health institutions to raise awareness and improve vaccination compliance in this population.